2007
DOI: 10.1161/hypertensionaha.107.089250
|View full text |Cite
|
Sign up to set email alerts
|

Heparin Impairs Glycocalyx Barrier Properties and Attenuates Shear Dependent Vasodilation in Mice

Abstract: Abstract-The endothelial glycocalyx is a hydrated mesh of polysaccharides and adsorbed plasma proteins that forms the true interface between the flowing blood and the endothelium. We hypothesized in the present study that competitive binding of heparin to glycocalyx-associated proteins would affect glycocalyx barrier properties and mechanotransduction of shear stress to the endothelium. In anesthetized mice, the clearance of 70-kDa dextrans from the circulation was increased (PϽ0.05 versus saline) 1 hour after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
100
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 74 publications
(113 citation statements)
references
References 45 publications
8
100
0
1
Order By: Relevance
“…This hypothesis fits with the study of Gritters et al, who previously demonstrated an effect of heparin during HD on proteoglycan-bound PF4 possibly due to LMWH-induced endothelial detachment [16]. VanTeeffelen et al showed in mice that a heparin challenge is associated with increased vascular leakage of dextrans and impaired arteriolar vasodilation during reactive hyperemia, suggesting that competitive binding of heparin to glycocalyx-associated proteins may affect glycocalyx barrier properties [29]. On the other hand, heparins were found to bind P-Selectin, and may thus play a protective role in the early process of leucocyte adhesion and thereby block the cascade of ESL alterations [30].…”
Section: Discussionsupporting
confidence: 88%
“…This hypothesis fits with the study of Gritters et al, who previously demonstrated an effect of heparin during HD on proteoglycan-bound PF4 possibly due to LMWH-induced endothelial detachment [16]. VanTeeffelen et al showed in mice that a heparin challenge is associated with increased vascular leakage of dextrans and impaired arteriolar vasodilation during reactive hyperemia, suggesting that competitive binding of heparin to glycocalyx-associated proteins may affect glycocalyx barrier properties [29]. On the other hand, heparins were found to bind P-Selectin, and may thus play a protective role in the early process of leucocyte adhesion and thereby block the cascade of ESL alterations [30].…”
Section: Discussionsupporting
confidence: 88%
“…Biopsies were taken from the transplanted kidneys at 10 min after reperfusion, and P-selectin expression on peritubular capillary endothelium was assessed using a semiquantitative score: 0, no staining; 1, mild staining of some capillaries; 2, moderate staining of most peritubular capillaries; and 3, intense staining of all peritubular capillaries. (14,19,23,40). Glycocalyx loss in ischemically injured kidneys is therefore expected to result in reduced nitric oxide production, which has indeed been observed in human kidney transplantations with delayed graft function (20).…”
Section: Discussionmentioning
confidence: 92%
“…However, glycosaminoglycans at high concentrations in the circulation could also bind to plasma proteins that normally bind to the glycocalyx, leading to destabilization of a healthy glycocalyx. 82 Such complex and opposing effects might necessitate monitor ing of glycocalyx function before treatment with glycos aminoglycans so as to determine whether an individual will benefit.…”
Section: Glycosaminoglycansmentioning
confidence: 99%